Reactivity of an amidinato silylene and germylene toward germanium(ii), tin(ii) and lead(ii) halides. Issue 11 (2nd March 2017) - Shan, Yu-Liang; Leong, Bi-Xiang; Xi, Hong-Wei; Ganguly, Rakesh; Li, Yongxin; Lim, Kok Hwa; So, Cheuk-Wai
Abstract : The reaction of the amidinato silicon(ii )1 and germanium(ii ) amide4 with PbBr2 and SnCl2 afforded the amidinato silylene–dibromoplumbylene3 and germylene–dichlorostannylene6 adducts, respectively. Abstract : The coordination chemistry of an amidinato silylene and germylene toward group 14 element(ii ) halides is described. The reaction of the amidinato silicon(ii ) amide [LSiN(SiMe3 )2 ] (1, L = PhC(N t Bu)2 ) with SnCl2 and PbBr2 afforded the amidinato silylene–dichlorostannylene and –dibromoplumbylene adducts [L{(Me3 Si)2 N}SiEX2 ] (E = Sn, X = Cl (2 ); E = Pb, X = Br (3 )), respectively, in which there is a lone pair of electrons on the Sn(ii ) and Pb(ii ) atoms. X-ray crystallography, NMR spectroscopy and theoretical studies show conclusively that the Si(ii )–E(ii ) bonds are donor–acceptor interactions. Similar electronic structures were found in the amidinato germylene–dichlorogermylene and –dichlorostannylene adducts [L{(Me3 Si)2 N}GeECl2 ] (E = Ge (5 ), Sn (6 )), which were prepared by treatment of the amidinato germanium(ii ) amide [LGeN(SiMe3 )2 ] (4 ) with GeCl2 ·dioxane and SnCl2, respectively.